At Jeppe : fostering an approach toward placemaking in the South African metropolis through the metamorphosis of a place of gathering - Van Rensburg, Rudolf Johannes (University of Pretoria, 2015)
Dissertation (MArch(Prof))--University of Pretoria, 2014.